2002
DOI: 10.1104/pp.001701
|View full text |Cite
|
Sign up to set email alerts
|

The 5′-Untranslated Region of the ntp303 Gene Strongly Enhances Translation during Pollen Tube Growth, But Not during Pollen Maturation

Abstract: Transcripts of the ntp303 gene accumulate abundantly throughout pollen development, whereas the protein only accumulates to detectable levels after pollen germination. In an attempt to explain the divergence in the accumulation profiles of the mRNA and the protein, we investigated the role of the untranslated regions (UTRs) in enhancing ntp303 translation during the transition from developing to germinating pollen. Luciferase reporter gene fusion constructs containing the ntp3035′-UTR gave rise to luciferase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…This gene is expressed in sporophytic tissues of the anther, mature pollen, and root caps, but also in the endosperm (Twell et al, 1991) and was shown recently to be a ligand of the pollen receptor kinase LePRK2 (Tang et al, 2002). Translational enhancement of the late pollen genes LAT52 and NTP303 has been reported to be mediated by their 5Ј-UTRs (Bate et al, 1996;Hulzink et al, 2002). Transient transformation assays with ZmMADS2 promoter deletion constructs revealed only slight differences in expression levels of the luciferase reporter gene either with or without 5Ј-UTR, indicating that the functional role of the 5Ј-UTR of ZmMADS2 is different.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is expressed in sporophytic tissues of the anther, mature pollen, and root caps, but also in the endosperm (Twell et al, 1991) and was shown recently to be a ligand of the pollen receptor kinase LePRK2 (Tang et al, 2002). Translational enhancement of the late pollen genes LAT52 and NTP303 has been reported to be mediated by their 5Ј-UTRs (Bate et al, 1996;Hulzink et al, 2002). Transient transformation assays with ZmMADS2 promoter deletion constructs revealed only slight differences in expression levels of the luciferase reporter gene either with or without 5Ј-UTR, indicating that the functional role of the 5Ј-UTR of ZmMADS2 is different.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the RNA folding predictions for the BnRop9 and Rop3 upstream regions showed little secondary structure. Perhaps, the folding in the pollenspeciWc ROP mRNA allows it to survive storage in (Hulzink et al 2002). The presence and absence of uORFs in members of the highly related ROP gene family might provide an interesting model system to explore the roles of these elements in gene regulation.…”
Section: ј Utrs and Gene Regulationmentioning
confidence: 98%
“…Bp10 from Brassica napus (ASO_BRANA), expressed in developing pollen, shows 30% sequence identity to ascorbate oxidase, but the copper-binding residues are not conserved [74]. The NTP303 gene is related to pollen tube growth and is expressed abundantly during pollen development [75]. The SKU5 gene from Arabidopsis thaliana codes another protein homologous to ascorbate oxidase, but it has no copper-binding center [76].…”
Section: Ascorbate Oxidase Homologues With No Blue Copper-binding Sitementioning
confidence: 99%